Governance in Peru : towards a republic for all - Velasco Fernández, Otoniel (2013)
Governance in the Republic is strongly influenced by history, which has its roots in the early Andean civilization that culminated in the Inca Empire or Tawantinsuyo, which formed an autarchic State in economic terms, with relative social welfare and despotic in political terms. Over the millennia, the Andeans developed technologies appropriate to their environment, occupied the territory rationally, established an immense network of roads and ensured sufficient food production to meet the needs of the population, despite the scarcity of agricultural land. Although they did not know writing, they created the "quipus", colored cords with different types of knots with which they could keep accounts and administer the vast territory they came to occupy (research is underway to prove that the qui pus were actually a writing system).